Robotic arm based companion system - Tay, Aloysius Zen (Nanyang Technological University, 2025)
This report presents the development of a 6 DOF robotic arm desktop companion that is designed to interact with the user, improving their physical health as well as their mental well-being. The robotic arm’s movements are controlled using forward and inverse kinematics, through the use of MATLAB to compute precise joint angles.